Horizontal and Vertical Distribution of Hazelnut Root System - Oparnica, Čedo; Radivojević, Dragan; Milićević, Magdalena; Tešić, Nemanja (Journal of Agricultural Sciences (Belgrade), 2026)
The application of agrotechnical and pomotechnical measures in modern fruit production depends on a thorough understanding of the morphological characteristics of both the above- and below-ground organs of hazelnut cultivars. This study aimed to determine the horizontal and vertical distribution of the root system in five-year-old bushes of the hazelnut cultivars Tonda di Giffoni and Tonda Gentile Romana. The research was conducted in a hazelnut orchard in Velika Krsna (Mladenovac, Serbia) in 2019. The results showed significant differences in root length depending on the distance from the trunk and soil depth in both cultivars. In Tonda di Giffoni, the greatest root length was recorded at a depth of 10–20 cm, reaching 1,914 cm (41%) at a distance of 200 cm from the trunk, while at 50–100 cm it was 861 cm (45%). Root length decreased with increasing distance and depth, whereas root diameter increased with depth but decreased with distance from the trunk. The total root length in this cultivar was 4,672 cm. In Tonda Gentile Romana, the total root length was higher, amounting to 7,212 cm. The highest root length was also observed at a depth of 10–20 cm, reaching 3,279 cm (45%), and 1,470 cm (45%) at 50–100 cm from the trunk. Root diameter increased with depth (2.35–18.5 mm), while the number of roots decreased. The results indicate that root system distribution is strongly dependent on cultivar.
Keywords: hazelnut; root system; horizontal and vertical distribution